Diagnostic yield and cost analysis of electrocardiographic screening in Swiss paediatric athletes - Albinski, M.; Saubade, M.; Menafoglio, A.; Meyer, P.; Capelli, B.; Perrin, T.; Trachsel, L.; Hagemeyer, D.; Casagrande, D.; Wilhelm, M.; Benaim, C.; Pirrello, T.; et al. (Journal of Science and Medicine in Sport, 2022)
Objectives: Athletes performing sports on high level are at increased risk for sudden cardiac death. This includes paediatric athletes, even though data on screening strategies in this age group remain scarce. This study aimed to assess electrocardiogram interpretation criteria in paediatric athletes and to evaluate the cost of screening. Methods: National, multicentre, retrospective, observational study on 891 athletes of paediatric age (<18 years) evaluated by history, physical examination and 12-lead electrocardiogram. The primary outcome measure was abnormal electrocardiogram findings according to the International Recommendations for Electrographic Interpretation in Athletes. The secondary outcome measure was cost of screening. Results: 19 athletes (2.1%) presented abnormal electrocardiogram findings requiring further investigations, mainly abnormal T-wave inversion. These 19 athletes were predominantly males, performing endurance sports with a mean volume of 10 weekly hours for a mean duration of 6 years of training. Further investigations did not identify any relevant pathology. All athletes were cleared for competition with regular follow-up. Total costs of the screening were 108,860 USD (122 USD per athlete). Conclusions: Our study using the International Recommendations for Electrographic Interpretation in Athletes identified a low count of abnormal findings in paediatric athletes, yet raising substantially the cost of screening. Hence, the utility of electrocardiogram-inclusive screening of paediatric athletes remains to be elucidated by longitudinal data.